Perancangan Instalasi Pengolahan Air Limbah (IPAL) Komunal di Perumahan Green Hills Recidence, Cilacap Utara, Cilacap - Rahmanda, Isyel Kayla; Nuranggraeni, Meita; Stevila, Mumpuni Lutfi; Hidayat, Ridho (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
Abstract: The increase in population greatly affects the decrease in the carrying capacity of the environment. This is because the population makes a significant contribution to waste generation. Most of the municipal sewage treatment plants are built with a combination of anaerobic-aerobic systems. This study aims to determine the debit for the type of gray water and type of black water, determine the pipe requirements to be used, to design a Communal WWTP design in the research location. The location where the Communal WWTP design will be carried out is Green Hills Residence, Tritih Lor, Kec. Jeruklegi, Cilacap Regency, Central Java. The area of the land area is around 1.5 hectares with a total of 39 houses. In the process of making planning the design of the Communal WWTP that is determined is the projection of population growth in the next 10 years, gray water waste discharge, black water waste discharge, piping calculations, and the dimensions of the tanks in the Communal WWTP. The debit for gray water is 96 liters/day/person and black water is 22.5 liters/day/person. The pipe requirements for one housing include 320 m of fecal pipes, 120 m of domestic pipes, 160 m of tertiary pipes for feces, and 60 m of tertiary pipes for domestic. The design of the Communal WWTP in the research location is designed to consist of two, namely for Gray Water and Black Water